Notes on Nearctic genera Catalinus Casey and Parascydmus Casey (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2019)
Morphological structures of several glandulariine genera known to occur only in North America have never been properly described and illustrated. In consequence, status and diagnoses of some potentially key taxa to understand the evolution of the Northern Hemisphere Scydmaeninae remain unclear. Comparative morphological study of Catalinus and Parascydmus is intended to reduce this gap. Examination of type species revealed that both genera belong to glandulariine taxa characterized by the submentum demarcated laterally by sutures. The status as separate genus for Catalinus and Parascydmus is maintained. The most interesting discovery is that the Nearctic Parascydmus resembles most the endemic Japanese Rutaraphes; among other characters, these taxa share a uniquely modified frons and the aedeagus lacking parameres.